ANALISIS EFEKTIVITAS KERJA PEGAWAI DI KANTOR CAMAT LONG PAHANGAI KABUPATEN MAHAKAM ULU - Marjoni Rachman Sophia Hipui (ADMINISTRASI PUBLIK, 2017)
This study aims to find and describe the Effectiveness of Employees in the Office of the Sub-District of Long Pahangai Mahakam Regency. The approach used in this research is qualitative descriptive approach. In this research will be a description of five indicators, namely Work Results, Number of Employees, Time, Cost and Job Satisfaction.The results showed that the effectiveness of Employees in the Office of the Sub-District of Long Pahangai Mahakam Regency obtained a score of 72.8% and this is included in the category quite well. Thus the formulation of problems and hypotheses in this study have been answered and proven well.